Optimizing the photon flux of double optical gated high-order harmonic spectra - Mashiko, Hiroki; Gilbertson, Steve; Li, Chengquan; Moon, Eric; Chang, Zenghu (My University, 2008)
The combination of polarization gating and two-color gating is a promising approach to generate single isolated attosecond pulses with multicycle pump lasers. We searched the phase-matching conditions for high-order harmonic generation with such a double optical gating using 0.85mJ, 8fs laser pulses centered at 790nm. At the optimized gas target location and pressure, the single extreme ultraviolet pulse energy is 6.5nJ for argon and 170 pJ for neon, which are much higher then those generated with conventional polarization gating. In addition, the carrier-envelope phase effects with a 2π periodicity were attained when the highest extreme ultraviolet photon flux was produced, indicating the robustness of the double optical gating.